Optimal number of endoscopic biopsies for diagnosis of early gastric cancer - Nishitani, Masaki (Endosc Int Open, 2019)
Background and study aims  No recommendations are available for optimal number of endoscopic biopsies for early gastric cancer (GC), and whether detection of early GC is improved by increasing the number of biopsy is unclear. We therefore evaluated the relationship between number of biopsies and diagnostic accuracy. Materials and methods  We retrospectively evaluated 858 early GCs (623 from endoscopic submucosal dissection and 235 surgical specimens), which we classified as obtained after one, two, or three or more biopsies. We assessed diagnostic accuracy by number of biopsies, and in subgroups by tumor diameter, gross type, and surface color. Results  Almost half the lesions were obtained after one biopsy each, 30 % after two biopsies, and 20 % after three or more biopsies. Although diagnostic accuracy increased with biopsy number, it was significantly greater for the two-biopsy group than the one-biopsy group, (92.5 % vs. 83.9 %, P  = 0.0009), but did not significantly differ between the two- and three or more-biopsy groups. This finding was seen when tumors were evaluated by size, but not by elevated type and surface color, for which more biopsies did not improve diagnostic accuracy. Multivariate analysis demonstrated that two or more biopsies was the independent significant factors for diagnostic accuracy. Conclusions  Two biopsies are the optimal number required to diagnose early GC.